French Colonization: A critical factor for democratization question in northern Africa - Λάττας, Νικόλαος (Πανεπιστήμιο Πελοποννήσου, 2022)
The main research question of the dissertation is wether the French colonization has had impact in the democratization process of the Maghreb states and if yes to what extent. The subject is approached through the historical course of the three countries and study of their social, political and economical situations.
Γαλλική Αποικιοκρατία: Ένας κρίσιμος παράγοντας για το ζήτημα εκδημοκρατισμού στη βόρεια Αφρική
Keywords: Γαλλία--Αποικίες--Ιστορία; Βόρεια Αφρική--Αποικίες; Εκδημοκρατισμός--Αφρική, Βόρεια; Γαλλική αποικιοκρατία; Εκδημοκρατισμός; Μαγκρέμπ; Μαρόκο; Τυνησία; Αλγερία; Γαλλία